The mean postpartum drop in the hemoglobin levels in a patient after delivery in the population attending a tertiary hospital in south Kerala - Viswanathan, Manjusha; Daniel, Suja; P., Nimmy; L., Manju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Post partum hemorrhage is still the major cause of maternal mortality and morbidity all around the world. Post partum anemia is a major outcome of postpartum hemorrhage and this affects the maternal health. Postpartum anemia is diagnosed when the adjusted Hb falls to <11 gm% in 24 hours, this impacts 80% of women in low- and middle-income countries. We hypothesize that more than anemia and blood loss it is the percentage drop in hemoglobin postnatally that affects the maternal health. Methods: The prospective observational study for a period of 1 year from January 2018 among the antenatal patients attending Sree Gokulam Medical College and Research Foundation, Kerala. 544 women were included in the study after applying the inclusion and exclusion criteria. The hemoglobin levels were estimated at the time of admission for labor and 48 hours postnatally. Statistical analysis was done and the mean hemoglobin drop post-partum was calculated in cases of normal delivery and in Caesarean section. Results: There is a mean drop of Hb of 0.237 (95% CI 0.091-0.383) with t value of 3.189 (p- value of 0.002) and the mean fall in Hb after CS is 0.604 with t value of 5.847 (95% CI 0.400-0.808) with percentage drop in Hb calculated as 5.09%. Conclusions: There is significant blood-loss not amounting to postpartum hemorrhage by definition but can affect the maternal health detrimentally.